Case report of a rare giant bone island in a vertebral body combined with hemangioma. Issue 5 (May 2021) - Gou, Qi; Huang, Hui; Wang, Yuecheng; Zeng, Rong; Zhou, Daiying; Huang, Xuemei; Chen, Dongmei; Ma, Tao; Liu, Qingshan
This case report describes a rare giant bone island combined with hemangioma diagnosed in a patient with osteolytic vertebral metastases. The bone island's greatest diameter was 3.15 cm, and bone islands of this size are rare in the literature. This article aims to provide clinicians with information about the diagnosis and relevant literature of bone islands.